The Psychometric Properties of Turkish Version of Depression Anxiety Stress Scale-21 (DASS-21) in Community and Clinical Samples - Hakan SARICAM (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
This paper presented the Turkish version of the Depression Anxiety Stress Scale-21 (DASS-21) in community and clinical samples, examined its psychometric properties. Construct validity and concurrent validity were conducted in validity studies. Depression Anxiety Stress Scale-42 (DASS-42) was used for concurrent validity. In reliability analysis, the instruments internal consistency and re-test reliability were studied. Results of explanatory factor analyses demonstrated that 21 items yielded three-factors. Results of confirmatory factor analyses for three-dimensional model showed that acceptable fit index values in community sample and perfect fit index values in clinical sample. Factor loadings ranged from .42 to .72. In the concurrent validity, significant positive relationships were found between DASS-42 and DASS-21. Cronbach alpha internal consistency coefficient was found as α= .87 for depression sub-scale, α= .85 for anxiety sub-scale and α= .81 for stress sub-scale in clinical sample. Moreover, test-retest reliability coefficient was obtained as r=.68 for depression sub-scale, r=.66 for anxiety sub-scale and r=.61 for stress sub-scale in community sample, and corrected item-total correlations ranged from .43 to .77 in clinical sample. In second study, DASS-21 discriminated the patients (depression mean score=10.83; anxiety mean score=10.39; stress mean score=11.85) from the healthy subjects (depression mean score=5.88; anxiety mean score=5.37; stress mean score=7.90) well (U=5310.50; 4748.50; 5562.50, p=0.00). According to psychometric properties, DASS-21 is a reliable and valid instrument in the assessment of depression, anxiety, stress levels. [JCBPR 2018; 7(1.000): 19-30]